Analysis Of Income And Added Value Of Cassava In Gedong Tataan District Pesawaran Regency - Lesta Apriyani, Nurya; Apriyani, Marlinda; Desfaryani, Rini; Marga Saty, Fadila (Jurnal Manajemen Agribisnis Terapan, 2025)
Cassava is a leading commodity in Lampung Province, but the selling price at the farmer level is often volatileand low. Processing cassava into chips is an alternative to increase income. This study analyzes the incomeand added value of cassava chip processing businesses in 15 MSMEs in Karanganyar Village, Gedong TataanDistrict, Pesawaran Regency using quantitative descriptive methods and Hayami calculations. The majorityof businesses use personal capital with a production capacity of 100-300 kg per day. The results show that theaverage net income of small-scale MSMEs reaches IDR 12,210,050 per month and large-scale MSMEs reachIDR 26,604,686 per month. The average added value for small-scale businesses is IDR 3,402 per kg with aratio of 57 percent, while for large-scale businesses it is IDR 3,784 per kg with a ratio of 60 percent. Thisproves that processing cassava into chips is feasible and profitable. Policy support, access to capital, training,and market expansion are needed to strengthen the competitiveness of MSMEs.